2015
DOI: 10.1161/circoutcomes.114.001177
|View full text |Cite|
|
Sign up to set email alerts
|

Conflicting Results Between Randomized Trials and Observational Studies on the Impact of Proton Pump Inhibitors on Cardiovascular Events When Coadministered With Dual Antiplatelet Therapy

Abstract: Background: Discordant results have been reported on the effects of concomitant use of proton pump inhibitors (PPIs) and dual antiplatelet therapy (DAPT) for cardiovascular outcomes. We conducted a systematic review comparing the effectiveness and safety of concomitant use of PPIs and DAPT in the postdischarge treatment of unstable angina/non-ST segment elevation myocardial infarction (UA/NSTEMI) patients. Methods and Results: We searched for clinical studies in MEDLINE, EMBASE, and the Cochrane Database of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 43 publications
(103 reference statements)
2
62
0
4
Order By: Relevance
“…Some pharmacologic studies led the FDA in 2009 to warn against combining Clopidogrel and PPIs. Conflicting clinical data have been published (Ho et al, 2009;Juurlink et al, 2009): one meta-analysis of 31 observational studies found that patients using PPIs with Clopidogrel have about a 30% increased risk of cardiovascular events compared with nonusers of PPIs, although the four randomized trials assessing Omeprazole or Esomeprazole did not confirm the increased risk (Melloni et al, 2015).…”
Section: Cardiovascular Eventsmentioning
confidence: 99%
“…Some pharmacologic studies led the FDA in 2009 to warn against combining Clopidogrel and PPIs. Conflicting clinical data have been published (Ho et al, 2009;Juurlink et al, 2009): one meta-analysis of 31 observational studies found that patients using PPIs with Clopidogrel have about a 30% increased risk of cardiovascular events compared with nonusers of PPIs, although the four randomized trials assessing Omeprazole or Esomeprazole did not confirm the increased risk (Melloni et al, 2015).…”
Section: Cardiovascular Eventsmentioning
confidence: 99%
“…As far as the inhibition of the CYP 2C19 by the PPI is reversible and considering the short half-life of the PPI, some authors suggested minimizing the clinical consequences of this interaction by prescribing the PPI in the morning and the clopidogrel in the evening with an interval of 12 hours by separating both the takings [55]. However, the published randomized forward-looking studies did not find this interaction and confirmed the beneficial effects of the PPI on the digestive bleedings [31,56,57,58]. In 2012, these data allowed Afssaps (become ANSM: National agency of Safety of the Medicine) to remove, the PPI-clopidogrel interaction from the thesaurus of the medicinal interactions [59].…”
Section: Esophageal Abnormalitiesmentioning
confidence: 99%
“…Finally, closely examine the event curves in the randomized trials included in the analysis by Melloni et al 1 These trials do not simply fail to confirm that a negative interaction might exist. The virtually superimposable strongly curves would seem to strongly refute that a clinically significant interaction exists at all.…”
Section: Berger Proton Pump Inhibitors and Clopidogrelmentioning
confidence: 99%
“…How can it be, then, that certain PPIs (and statins and calcium channel blockers) inhibit the ex vivo inhibition of aggregation (they do), and reduce the level of clopidogrel's active metabolite (they do), but do not reduce the efficacy of clopidogrel? 1,2,7 The answer is not entirely clear. Possible explanations include that the reduction in inhibition of aggregation (and levels of active metabolite) are too small to be clinically significant and that perhaps the relationship between ex vivo aggregability (and metabolite levels) and risk of thrombosis is curvilinear rather than linear.…”
Section: Berger Proton Pump Inhibitors and Clopidogrelmentioning
confidence: 99%
See 1 more Smart Citation